A Study on The Potential Pathways For Existing Drugs Against COVID-19 - Mansur, Sity Aishah; Mohamed Rehan, ‘Aisyah (Journal of Advanced Industrial Technology and Application, 2021)
Coronavirus infectious disease 2019 (COVID-19) is a global pandemic declared by the World Health Organization (WHO) in March 2020. This emerging infectious disease is rapidly transmitted and does not only pose a global threat to public health but also badly affects the economy. At present, there is no effective drug to treat COVID-19, leading to a significant challenge upon current global attempts at restraining the outbreak. There are several currently available drugs, also considered as the repurposed drugs are in use for treatment against COVID-19. However, these drugs are not as efficient as it is hoped. Therefore, this study is conducted to further explore into other established antivirus that could function better for COVID-19 treatment. In addition, the pathways that associated with the drugs are identified and potential targeted proteins for the repurposed drugs are also pointed out. The articles for review were selected from several search engine databases, which are ScienceDirect, SpringerLink, PubMed, and Scopus including the keywords COVID-19, SARS, MERS, potential pathways for antiviral drugs as well as repurposed drugs, with more than 50 primary research articles identified. Findings and analysis have discovered potential repurposed drugs that could be used for COVID-19, namely bisoxatin, nitazoxanide and teicoplanin which could be involved in corona-related pathways. Meanwhile, the associated pathways are JAK-STAT, Neprilysin (NEP) and cGAS-STING that counteract excessive immune response and act as a medium for the drugs to access antiviral activities. The repurposed drugs target protein identification is also a critical significance and it was found that S-protein, TMPRSS2, RdRp and RDB which are the signalling protein can be interrupted by the repurposed drugs, presenting a promising antivirus against SARS-CoV-2. It is concluded that this study will provide information to assist logical design of the repurposed drug for its effectiveness as antivirus against COVID-19.